(untitled) (Journal of Asian Development Studies, 2023)
Medication errors occur during patient care and are widely reported globally. They pose a serious threat to patient safety. Accordingly, the present study has attempted to examine the influence of knowledge, attitude, and behaviour about intravenous medication error administration on intravenous medication errors. The study followed a quantitative deductive approach. Data were collected from the nurses working in Lahore General Hospital. The total population was 408 nurses. The sample size for the present study was 200 working in the general ward, emergency, intensive care, and operation theatres, among other departments. Data were collected using the questionnaire, and all the questions were adapted from the previous studies. Collected data were subjected to SPSS for analysis. Results of the study revealed that knowledge and behaviour regarding intravenous medication administration have a significant influence on medication errors. At the same time, On the other hand, attitude was not found to influence intravenous medication errors significantly. The study offers valuable insights into the theory and practice.